2019
DOI: 10.1590/1806-9061-2018-0903
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Dietary Supplementation of Lactobacillus plantarum, and Fermented and Non-Fermented Artemisia Annua on the Performance, Egg Quality, Serum Cholesterol, and Eggyolk-Oxidative Stability During Storage in Laying Hens

Abstract: Artemisia annua L. is a widely distributed medicinal plant and well-known for treating malaria due to the artemisinin content. We previously found enhanced antioxidant and antibacterial activities of Lactobacillus plantarum-fermented A. annua dried leaves in vitro. The present study compared the effects of the dietary supplementation of L. plantarum, fermented (FA) or non-fermented (NFA) A. annua on laying performance, egg quality, serum cholesterol, and egg yolk oxidative stability during storage in 40-weeks-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…The Haugh unit and albumen height are important indexes for measuring the internal quality of eggs. The higher Haugh unit in the 2% fermented AAR group of the present study was consistent with the findings of Lee et al [41], who found that the supplementation of Artemisia annua increased the Haugh unit of eggs (3 weeks), which may have been caused by the active substances in the fermented AAR that improve the oxidative stability and prolong the freshness period of eggs. However, we found that there was no significant difference in yolk color, which was not consistent with Baghban-Kanani et al [20], who found that supplementation of Artemisia annua led to an increase in yolk color, which might be due to the degradation of pigments caused by fermentation or the low content of pigments in the AAR in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…The Haugh unit and albumen height are important indexes for measuring the internal quality of eggs. The higher Haugh unit in the 2% fermented AAR group of the present study was consistent with the findings of Lee et al [41], who found that the supplementation of Artemisia annua increased the Haugh unit of eggs (3 weeks), which may have been caused by the active substances in the fermented AAR that improve the oxidative stability and prolong the freshness period of eggs. However, we found that there was no significant difference in yolk color, which was not consistent with Baghban-Kanani et al [20], who found that supplementation of Artemisia annua led to an increase in yolk color, which might be due to the degradation of pigments caused by fermentation or the low content of pigments in the AAR in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Fermentation has been found to improve nutritional and functional values of TLMs as well as enhance performance parameters and product quality of broilers (Sugiharto and Ranjitkar 2019 ; Shi et al 2021 ). Fermented TLM has also been reported to improve productivity of animals other than broilers (Zhou et al 2015 ; Lee et al 2019 ). However, there are variable results on the impacts of dietary fermented TLM on broiler productivity and meat quality (Cao et al 2012 ; Mandey et al 2015 ; Santoso et al 2015 , 2018 ; Kim et al 2017 ; Manihuruk et al 2018 ; Niu et al 2019 ), and this discrepancy could be attributed to differences in broiler genetics, microorganisms implicated in the fermentation process, substrate used, composition of TLM, quantity of TLM incorporated into the diet and several other factors known to affect chicken performance (Ditengou et al 2023 ; Ogbuewu and Mbajiorgu 2023 ).…”
Section: Introductionmentioning
confidence: 99%